At the beginning was the decree. Towards a shared design process between insiders and outsiders - Loretta Fabbri; Mario Giampaolo; Alessandra Romano (Firenze University Press, 2018)
The article describes the collaborative research carried out for the co-design of the Program for professional socio-pedagogical educator. Starting from the analysis of the laws and regulations defining normative parameters, using the results of the TECO-D project, the work reconstructs the elements of the research conducted with educators working in the professional sectors interested by the Program. The collaborative methodology implemented has made possible identifying four core contents: situated theories, methodologies of investigation, verification of the effectiveness of the educational action, conflicts between colleagues.   In principio era il decreto. Verso una progettazione condivisa tra insider e outsider Il contributo descrive la ricerca collaborativa condotta per la co-progettazione del Corso intensivo di formazione per la qualifica di educatore professionale socio-pedagogico. Partendo dall'analisi della traiettoria legislativa che ne ha definito normativamente i parametri, utilizzando il lavoro di ricerca svolto nel progetto TECO-D, si arriva a ricostruire gli elementi della ricerca condotta insieme ad educatori e coordinatori dei servizi che operano nei settori professionali interessati dal corso di formazione. La metodologia collaborativa attuata ha permesso di individuare quattro contenuti ritenuti centrali dai partecipanti alla ricerca: Teorie situate, metodologie d'indagine, verifica dell'efficacia dell'azione educativa, conflitti tra colleghi.